A new dawn. A Reading of the Idea of Hope in S. Kierkegaard’s Thought - Garrido Maturano, Ángel E. (Revista de Filosofía, 2017)
The article attempts to offer a phenomenological and hermeneutical reading of the problem of hope in Kierkegaard’s thought. First, it grounds the peculiar legitimacy of the phenomenon in the notion of spirit. Second, in philosophical terms, it elucidates the hope in the realm of God as an ontogenetic correlation that is realized in a process. Then, it analyzes silence, obedience, and happiness as indications of the experience of hope. Finally, it specifies the temporality and the aesthetic dimension of the phenomenon.
Keywords: Kierkegaard; hope; being; spirit; present.